Musical Development Of Barongan Turonggo Laras Through Additional Instrument In Kendal Regency (Jurnal Seni Musik, 2021)
This study aims to determine, describe, and analyze the development of the Barongan work of the Turonggo Laras group in Kendal Regency. The method used is descriptive qualitative with a musicological approach. Data collection techniques include observation, interviews, and documentation. The results showed that the development of working on Barongan Turonggo Laras music was in the form of adding western musical instruments, such as drums and keyboards in collaboration with gamelan. The use of the keyboard is intended as a filler for the main melody in campursari songs. This is because there are tones in the campursari song that does not exist on the gamelan instrument but exist on the keyboard. The addition of drums in the show is intended to lift the mood and strengthen the trance scene. The drum play tends to follow the dynamics of the kendang when accompanying the performance.